2009
DOI: 10.1182/blood-2008-06-163121
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory tachykinins that signal through the neurokinin 1 receptor promote survival of dendritic cells and potent cellular immunity

Abstract: IntroductionBecause of their crucial role in initiation and control of innate and adaptive immunity, myeloid dendritic cells (DCs) are the preferred target Ag-presenting cells for positive cellular vaccination protocols. 1 During the past decade, ex vivo-generated DCs have been used in immunization approaches for prevention and treatment of cancer and infectious diseases. 2 Current DC-based vaccines focus on the adjuvant effect of proinflammatory mediators, conferring DCs the capability to initiate and bias T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 78 publications
4
52
1
Order By: Relevance
“…Consistent with this notion, we were able to detect NK-1 but not NK-2 or NK-3 mRNA in B cells (data not shown). Like in many other assays (21,23,25,26,42,43), HK-1 activity on B cells could be fully reproduced with SP, which is in accord with several earlier reports documenting enhanced Ig secretion in the presence of SP (44). Given the apparent functional overlap, an important issue is the tissue distribution of the two peptides.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Consistent with this notion, we were able to detect NK-1 but not NK-2 or NK-3 mRNA in B cells (data not shown). Like in many other assays (21,23,25,26,42,43), HK-1 activity on B cells could be fully reproduced with SP, which is in accord with several earlier reports documenting enhanced Ig secretion in the presence of SP (44). Given the apparent functional overlap, an important issue is the tissue distribution of the two peptides.…”
Section: Discussionsupporting
confidence: 77%
“…Other than Ca 2+ mobilization, little is known about HK-1 signaling. Several studies have demonstrated that SP or its analog induced ERK phosphorylation, protein kinase C translocation, or the activation of the PI3K-Akt pathway in different cell types (43,48). In this study, we showed that HK-1 was a potent activator of the MAPKs in B cells.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The NK-1 receptor, the preferred receptor of SP, mediates a variety of physiological and pathophysiological responses (22,23,43). Although previous studies have confirmed that SP enhances corneal epithelial migration when combined with IGF-1 or EGF (41,44,45), the exact mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, SP causes the mobilization of bone marrowderived stem cells to participate in corneal wound healing (19,20). Interestingly, recent evidences have shown that SP activates the EGFR, mitogen-activated protein kinases (MAPKs), extracellular signal-regulated kinases (ERKs), and phosphoinositide 3-kinase-Akt (PI3K-Akt) signaling pathways, as well as promotes the healing of inflamed colonic epithelium (21) and possesses antiapoptotic effects in colonocytes (22), dendritic cells (23), tenocytes (24), neutrophils (25), and bone marrow-derived stem cells (26).…”
mentioning
confidence: 99%